Politics and Emotions in Romantic Periodicals
XIII, 244 p. 3 illus.
Keywords: This book comprises eleven essays by leading scholars of early nineteenth-century British literature and periodical culture. The collection addresses the many and varied links between politics and the emotions in Romantic periodicals, from the revolutionary decade of the 1790s, to the 1832 Reform Bill. In so doing, it deepens our understanding of the often conflicted relations between politics and feelings, and raises questions relevant to contemporary debates on affect studies and their relation to political criticism. The respective chapters explore both the politics of emotion and the emotional register of political discussion in radical, reformist and conservative periodicals. They are arranged chronologically, covering periodicals from Pigs’ Meat to Blackwood’s Edinburgh Magazine and The Spectator. Recurring themes include the contested place of emotion in radical political discourse; the role of the periodical in mediating action and performance; the changing affective frameworks of cultural politics (especially concerning gender and nation), and the shifting terrain of what constitutes appropriate emotion in public political discourse. Jock Macleod is Associate Professor of Literary Studies at Griffith University. William Christie is Professor and Director of the Humanities Research Centre at the Australian National University. Peter Denney is Senior Lecturer in History at Griffith University.